2004
DOI: 10.7326/0003-4819-140-11-200406010-00013
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review: Surveillance Systems for Early Detection of Bioterrorism-Related Diseases

Abstract: Few surveillance systems have been specifically designed for collecting and analyzing data for the early detection of a bioterrorist event. Because current evaluations of surveillance systems for detecting bioterrorism and emerging infections are insufficient to characterize the timeliness or sensitivity and specificity, clinical and public health decision making based on these systems may be compromised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
161
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(162 citation statements)
references
References 97 publications
0
161
0
1
Order By: Relevance
“…During the past decade, increased awareness of the need to recognize the introduction of pathogens in a monitored population as early as possible has caused a shift in disease surveillance towards systems that can provide timely detection [1,2]. Some monitoring has shifted to pre-diagnostic data, which are available early, but lack specificity for the detection of particular diseases.…”
Section: Introductionmentioning
confidence: 99%
“…During the past decade, increased awareness of the need to recognize the introduction of pathogens in a monitored population as early as possible has caused a shift in disease surveillance towards systems that can provide timely detection [1,2]. Some monitoring has shifted to pre-diagnostic data, which are available early, but lack specificity for the detection of particular diseases.…”
Section: Introductionmentioning
confidence: 99%
“…on real-time data from the Department of Defense Military Health System [6] and BioSense, based on data from the Department of Veterans Affairs, the Department of Defense, retail pharmacies, and Laboratory Corporation of America [7]. These systems are designed to facilitate early detection of disease outbreaks as well as response to harmful health effects, exposure to disease, or related hazardous conditions.…”
Section: Author Summarymentioning
confidence: 99%
“…Situational awareness is the real-time analysis and display of health data to monitor the location, magnitude, and spread of an outbreak. As Bravata et al (2004) said, "...an essential component of preparations for illnesses and syndromes potentially related to bioterrorism includes the deployment of surveillance systems that can rapidly detect and monitor [emphasis added] the course of an outbreak and thus minimize associated morbidity and mortality. "…”
Section: Introductionmentioning
confidence: 99%
“…Sosin (2005) states that approximately 100 state and local health jurisdictions were conducting some form of syndromic surveillance in 2003, Bravata et al (2004 conducted a systematic review of the publicly available literature and various websites from which they identified 115 biosurveillance systems.…”
Section: Introductionmentioning
confidence: 99%